2006
DOI: 10.1073/pnas.0508606103
|View full text |Cite
|
Sign up to set email alerts
|

Direct phosphorylation and regulation of poly(ADP-ribose) polymerase-1 by extracellular signal-regulated kinases 1/2

Abstract: Sustained activation of poly(ADP-ribose) polymerase-1 (PARP-1) and extracellular signal-regulated kinases 1͞2 (ERK1͞2) both promote neuronal death. Here we identify a direct link between these two cell death pathways. In a rat model of hypoglycemic brain injury, neuronal PARP-1 activation and subsequent neuronal death were blocked by the ERK1͞2 inhibitor 2-(2-amino-3-methoxyphenyl)-4H-1-benzopyran-4-one (PD98059). In neuron cultures, PARP-1-mediated neuronal death induced by N-methyl-Daspartate, peroxynitrite,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
178
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(193 citation statements)
references
References 44 publications
10
178
0
Order By: Relevance
“…150 The MAPK/ ERK signaling pathway may also regulate inflammation through its effects on PARP-1 activation, which (as detailed later in this review) is an important modulator of proinflammatory gene expression. 151 Pharmacological inhibition of both the p38 152,153 and the MAPK/ERK 154 signaling pathways improves outcomes in a mouse model of ischemia-reperfusion, but the extent to which these effects are due to reduced inflammation has not been established.…”
Section: Mitogen-activated Protein Kinase (Mapk) Cascadementioning
confidence: 99%
“…150 The MAPK/ ERK signaling pathway may also regulate inflammation through its effects on PARP-1 activation, which (as detailed later in this review) is an important modulator of proinflammatory gene expression. 151 Pharmacological inhibition of both the p38 152,153 and the MAPK/ERK 154 signaling pathways improves outcomes in a mouse model of ischemia-reperfusion, but the extent to which these effects are due to reduced inflammation has not been established.…”
Section: Mitogen-activated Protein Kinase (Mapk) Cascadementioning
confidence: 99%
“…Thus, it seems that dephosphorylation of PARP-1 by PP5 facilitates PARP-1 activity or PARP-1 activation. The work of other groups and our preliminary analysis indicates that PARP-1 is phoshosphorylated on many sites (Kauppinen et al, 2006, data not shown). It will be interesting to identify the specific sites that are dephosphorylated by PP5 and to determine how they affect PARP-1 activity.…”
Section: Discussionmentioning
confidence: 50%
“…It has been suggested previously that phosphorylation may regulate PARP-1 activity (Kauppinen et al, 2006;Midorikawa et al, 2006). As it seemed that neither ATM-initiated signaling nor DNA-PK influenced activation of PARP-1 in response …”
Section: Activation Of Parp-1 After Bleomycin Treatment Depends On Pp5mentioning
confidence: 95%
See 1 more Smart Citation
“…Mechanisms underlying PARP1-mediated necroptotic cell death include cellular metabolic insufficiency (due to NAD and ATP depletion), PARinduced nuclear translocation of AIF (apoptosis inducing factor), and interference with prosurvival and prodeath signaling pathways [11,[17][18][19]. As for the latter, signaling routes mediated by MAP kinases have been shown to be intertwined with PARylation [20][21][22][23]. Of note, it has been shown that the expression of MAP kinase phosphatase 1 (MKP-1) is negatively regulated by PARP1 strengthening prodeath pathways mediated by JNK and p38 MAP kinases [24].…”
Section: Introductionmentioning
confidence: 99%